Digital Makeover - Collin, Béatrice; Taillard, Marie (Ascent Audio, 2021)
Digital Makeover: How L'Oreal Put People First to Build a Beauty Tech Powerhouse examines L'Oreal's successful people-driven digital transformation. Professors and authors Beatrice Collin and Marie Taillard set out exactly how L'Oreal turned itself into a digital and tech powerhouse by building on its legacy to reimagine relationships inside the company, and with its customers and partners. Digital Makeover comprehensively describes L'Oreal's strategy, including: - Maintaining market leadership in the face of disruption - Believing in the transformative power of the organization, its legacy, and its people - A social-centric approach to beauty tech, ecommerce, and digital services - The company's successful play for market dominance in China Case studies that showcase best practices for digital transformation across sectors Digital Makeover is perfect for anyone interested in business strategy, marketing, or digital transformation, as well as businesspeople and leaders from inside and outside the beauty industry, and belongs on the shelves of anyone with an interest in organizational transformation, management, leadership, and digital strategies.